Legal maxim: “Every loan that brings benefit is usury,” its related issues and implementation in pre-Islamic and Malaysian financial transactions - Amanullah, Muhammad (International Islamic University Malaysia, 2018)
An important Islamic legal maxim is “Every loan that brings benefit is usury”. A normal ruling of the Sharῑ‘ah is that if anyone receives a loan from a person or a bank, he is supposed to return its exact amount to the moneylender. Any increase to it is considered usury (ribᾱ’) and therefore forbidden. However, jurists dispute over the following issue: “If this increase is not stipulated at the time of giving the loan, and the borrower gives it at the time of paying the loan back to the lender.” Some jurists maintain that this is lawful, while others consider it as forbidden. Using descriptive and analytical methods, this paper discusses this legal maxim, its proofs, and the disputes of jurists on its related issues, while placing emphasis on the stronger opinion. It then strives to discuss its implementation in some pre-Islamic and Malaysian financial transactions.